2020
DOI: 10.3390/math8091536
|View full text |Cite
|
Sign up to set email alerts
|

Cryptobiometrics for the Generation of Cancellable Symmetric and Asymmetric Ciphers with Perfect Secrecy

Abstract: Security objectives are the triad of confidentiality, integrity, and authentication, which may be extended with availability, utility, and control. In order to achieve these goals, cryptobiometrics is essential. It is desirable that a number of characteristics are further met, such as cancellation, irrevocability, unlinkability, irreversibility, variability, reliability, and biometric bit-length. To this end, we designed a cryptobiometrics system featuring the above-mentioned characteristics, in order to gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 94 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…For example, Kwon et al [11] suggested a model that focuses more on the sentiment information of the raw data, and they sampled from the raw data as the input to the model. Jara-Vera et al [12] instead used a specific representation of the audio recording as input to the model. Following the extensive expansion of the deep learning technology in the domain of speech sentiment analysis, researchers can extract higher-level features from speech signals and can obtain better accuracy and recognition rates compared to lower-level features [13].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kwon et al [11] suggested a model that focuses more on the sentiment information of the raw data, and they sampled from the raw data as the input to the model. Jara-Vera et al [12] instead used a specific representation of the audio recording as input to the model. Following the extensive expansion of the deep learning technology in the domain of speech sentiment analysis, researchers can extract higher-level features from speech signals and can obtain better accuracy and recognition rates compared to lower-level features [13].…”
Section: Introductionmentioning
confidence: 99%
“…These models are fundamentally different in nature. For example, one group designed a DNN model that detects significant cues from raw audio samples [2], and another group utilized a particular representation of an audio recording to provide input for the model [12]. In order to make a robust and a significant model, the researchers utilized different types of feature combinations using diverse network strategies.…”
Section: Introductionmentioning
confidence: 99%